2011
DOI: 10.1007/s10534-011-9476-8
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione: a key component of the cytoplasmic labile iron pool

Abstract: The cytoplasmic labile iron pool supplies iron to the mitochondrion for heme and iron sulfur cluster synthesis and to many cytoplasmic enzymes, thereby controlling numerous metabolic reactions. Surprisingly the chemical nature of this pool has never been convincingly characterised. Here we provide evidence for iron(II)glutathione being the dominant component of this pool. We report for the first time the affinity constant for the glutathione-iron(II) interaction and use this value to study the cytoplasmic spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
183
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(202 citation statements)
references
References 50 publications
6
183
0
Order By: Relevance
“…We first focused on the possible involvement of cytosolic iron binding ligands in iron trafficking, like the highly prevalent GSH (Hider and Kong 2011) and the recently proposed mammalian siderophore 2,5-DHBA (Devireddy et al 2010). We found that[90% depletion of GSH in intact K562 cells did not affect iron uptake (from TfFe) into cytosol or mitochondria of intact cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We first focused on the possible involvement of cytosolic iron binding ligands in iron trafficking, like the highly prevalent GSH (Hider and Kong 2011) and the recently proposed mammalian siderophore 2,5-DHBA (Devireddy et al 2010). We found that[90% depletion of GSH in intact K562 cells did not affect iron uptake (from TfFe) into cytosol or mitochondria of intact cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As reduced glutathione GSH was proposed to act as a major component of cellular labile iron pools (Hider and Kong 2011), we assessed whether depletion of intracellular GSH levels might affect those putative pools and thereby iron delivery to cytosol and mitochondria. Though BSO pretreatment of K562 cells led to a major reduction (0.14 ± 0.003 nmol/ 10 6 cells in control untreated cells compared to 0.0003 ± 0.0001 nmol/10 6 cells, [90% reduction) in intracellular GSH levels, it failed to reduce iron ingress derived from TfFe either in the cytosol (Fig.…”
Section: Cell Reductive Environmentmentioning
confidence: 99%
“…Quantitative data on free cellular iron is limited. In normal mammalian cells, free [Fe 2þ ] is approximately 0.5-1.0 μM measured by fluorescence quenching analysis using calcein (35) and more recently, by potentiometric methods (36)…”
Section: Discussionmentioning
confidence: 99%
“…Recently, GSH has been proposed to be the major chelating agent of the labile iron pool (34) and to be absolutely indispensable for intracellular iron homeostasis and cytosolic ISC maturation (45). Thus, our finding that a stable T(SH) 2 -ISC complex can be formed in vitro poses a new biological role for T(SH) 2 in the iron-sulfur metabolism of trypanosomatids, either as a ligand of ISC proteins or as an intracellular ISC carrier, as recently proposed for GSH (65).…”
mentioning
confidence: 99%